Torenia sp. Extracts Contain Multiple Potent Antitumor Compounds with Nematocidal Activity, Triggering an Activated DNA Damage Checkpoint and Defective Meiotic Progression - Qinghao Meng; Robert P. Borris; Hyun-Min Kim (MDPI AG, 2024)
Previously, we analyzed 316 herbal extracts to evaluate their potential nematocidal properties in Caenorhabditis elegans. In this study, our attention was directed towards Torenia sp., resulting in reduced survival and heightened larval arrest/lethality, alongside a noticeable decrease in DAPI-stained bivalent structures and disrupted meiotic progression, thus disrupting developmental processes. Notably, Torenia sp. extracts activated a DNA damage checkpoint response via the ATM/ATR and CHK-1 pathways, hindering germline development. LC-MS analysis revealed 13 compounds in the Torenia sp. extracts, including flavonoids, terpenoids, tanshinones, an analog of resveratrol, iridoids, carotenoids, fatty acids, and alkaloids. Of these, 10 are known for their antitumor activity, suggesting the potential of Torenia species beyond traditional gardening, extending into pharmaceutical and therapeutic applications.